The Relationship between Spiritual Health and Fertility Preferences among Students of Selected Higher Education Centers, Mashhad, Iran - Mohammad Hasan Movahedi Shakib; Gholamhosein Zarifnejad; Seyed Reza Mazloom; Talat khadivzadeh (Mashhad University of Medical Sciences, 2021)
Background & aim: Considering the importance of keeping the country population young and fertility control, particularly, in the elites and with regard to the influence of spiritual well-being on fertility behaviour and childbearing in the religious cultural context of Iran, the present study aimed to determine the relationship between spiritual well-being and fertility preferences in the selected higher education centers of Mashhad, Iran in 2019. Methods: This correlational study was carried out on 296 married students of Mashhad University of Medical Sciences and Razavi University of Medical Sciences in Mashhad, Iran, who were selected using multistage sampling between 2018 and 2019. The data were collected using three questionnaires of individual-educational characteristics, spiritual health, and Miller's Fertility Preferences and Childbearing Questionnaire. The data were analyzed using descriptive statistics and Pearson's correlation coefficient. Results: In terms of spiritual health, 222 (75.0%) students had a moderately score. Also, 143 (48.3%) subjects had a high level of willingness to have children. Regarding the number of children, 88 (29.7%) students tended to have two children, and 75 (25.9%) participants were inclined to have children within 1 to 2 years after marriage. There was a significant linear relationship between the spiritual health and fertility preferences of the students (r=0.29; p <0.001). Conclusion: It is recommended to develop a codified and local curriculum for the education of spiritual health, and its impact on the fertility preferences of the students. However, further studies in this regard are suggested.